Hybrid fiber alterations in exercising seniors suggest contribution to fast‐to‐slow muscle fiber shift. Issue 3 (25th March 2019) - Moreillon, Maxime; Conde Alonso, Sonia; Broskey, Nicholas T.; Greggio, Chiara; Besson, Cyril; Rousson, Valentin; Amati, Francesca
Abstract: Background: Human skeletal muscle is composed of a functional and metabolic continuum of slow (Type I) and fast fibers (IIa and IIx). Hybrid fibers co‐expressing different myosin heavy chains are also present and seem to be more prominent in aging muscle. Their role is debated; hybrid fibers were reported either in a transitional state, between slow and fast fibers, or as fixed individual entities. This study examined the fate of hybrid fibers with an endurance exercise intervention in an elderly sedentary population. Methods: Twenty‐two sedentary healthy elderly men and women underwent a 16‐week supervised endurance exercise intervention. Eighteen endurance‐trained age‐ and gender‐matched volunteers served as controls. Fiber type distribution was determined by immunohistochemistry on vastus lateralis muscle biopsies pre‐intervention and post‐intervention. Results: A total of 13840 fibers were analyzed. At baseline, a Type II dominant fiber profile was observed compared with the control group, with more Type IIa ( P  = 0.0301) and Type IIx fibers ( P  = 0.0328). Hybrid fibers represented almost 5% of total muscle fibers in both groups. There was no significant difference between groups (I–IIa, P  = 0.6719 and IIa–IIx, P  = 0.0998). Intervention triggered qualitative dynamics towards an increase in Type I, and decrease in Type II fibers, paralleled by an increase in I–IIa hybrids ( P  = 0.0301). Conclusions: The present study is, to our knowledge, the first to examine hybrid muscle fiber type adaptations to an endurance exercise intervention in the elderly. Hybrid fiber proportions did not differ between chronic sedentary state and chronic endurance‐trained state. Exercise intervention increased Type I–IIa hybrid fibers along with shift dynamics in other fiber types suggesting the contribution of hybrid fiber to a fast‐to‐slow fiber type transition, eventually serving as intermediate reservoir from one monomorphic myosin heavy chain expressing fiber type to another. This finding favours the transitional theory regarding hybrid muscle fibers and exercise, crucial to understanding reversible mechanisms of sarcopenia and development of prevention measures.